2021
DOI: 10.1007/s00726-021-03002-x
|View full text |Cite
|
Sign up to set email alerts
|

Determination of amino acids in human biological fluids by high-performance liquid chromatography: critical review

Abstract: The quantitation and qualification of amino acids are most commonly used in clinical and epidemiological studies, and provide an excellent way of monitoring compounds in human fluids which have not been monitored previously, to prevent some diseases. Because of this, it is not surprising that scientific interest in evaluating these compounds has resurfaced in recent years and has precipitated the development of a multitude of new analytical techniques. This review considers recent developments in HPLC analytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…Native and derivatized biological amino acids, their PTM metabolites and AGEs are measured by many different liquid chromatographic (LC), gas chromatographic (GC) and electrophoretic techniques coupled with various detection techniques. They include visible, ultraviolet absorbance and fluorescence detection, as well as mass spectrometry (MS) and tandem mass spectrometry (MS/MS) as separation techniques, such as GC–MS and LC–MS/MS (Martens-Lobenhoffer and Bode-Böger 2014 ; Hušek et al 2016 ; Rabbani and Thornalley 2020 ; Gałęzowska et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Native and derivatized biological amino acids, their PTM metabolites and AGEs are measured by many different liquid chromatographic (LC), gas chromatographic (GC) and electrophoretic techniques coupled with various detection techniques. They include visible, ultraviolet absorbance and fluorescence detection, as well as mass spectrometry (MS) and tandem mass spectrometry (MS/MS) as separation techniques, such as GC–MS and LC–MS/MS (Martens-Lobenhoffer and Bode-Böger 2014 ; Hušek et al 2016 ; Rabbani and Thornalley 2020 ; Gałęzowska et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The measurement of FAAs and protein-AAs in biofluids is of utmost importance for nutritional, bio-chemical and metabolic studies, with a fundamental role in the diagnosis and monitoring of inherited disorders of metabolism [39]. Determining the level of FAAs in biofluids is also important for monitoring the effectiveness of dietary interventions in livestock animals [2,3].…”
Section: Discussionmentioning
confidence: 99%
“…Since AAs are the precursors of many biomarkers, determining the amount of AAs in biological fluids is essential for the early diagnosis of many diseases. Studies have reported that many AAs play a role in forming diseases such as phenylketonuria, citrullinemia, and homocystinuria diseases [58,59].…”
Section: Routine Methods For Detection Of Aas Proteins and Peptidesmentioning
confidence: 99%